Chiral Modulation from Molecular to Macroscopic levels by synthetic chiral-amide-bonded porphyrin dimers. (December 2019) - Liang, Xu; Qin, Mingfeng; Zhang, Xiaomei; Mack, John; Soy, Rodah C.; Nyokong, Tebello; Zhu, Weihua
Abstract: Six different nanoarchitectures were constructed by a series of synthetic bio-inspired chiral porphyrin dimers through molecular self-assembly behaviour. A plausible mechanism of chiral expression from the molecular to the macroscopic levels was investigated through an analysis of the optical spectroscopy and theoretical calculations. Highlights: Six different nanoarchitectures were constructed by chiral porphyrin dimers. The optical spectroscopic properties and TD-DFT calculation were carried out. The plausible mechanism of chiral expression was explored.